Effectiveness of Financial Management at the Department of Finance and Revenue Management Regional Property Tomohon. - Nangka, Nadia Gabriela; Mandey, Jantje; Tampi, Gustaf Budi (Sam Ratulangi University, 2015)
ABSTRACT Reform of financial management can’t be separated from the purpose regional autonomy itself, which in addition to improving public services, both qualitatively and quantitatively, also in order to allocate resources efficiently and effectively, as well as the achievement of the space for public participation in developing regions. The principles of financial management, namely accountability, honesty in managing finances, transparent, and responsible in observing the principle of fairness, compliance, and benefits to society. Needed a system that could provide reasonable assurance that the implementation of the activities at a Government Agency can achieve the objectives efficiently and effectively, financial management report are reliable, secure state assets, and encourage adherence to regulations. This system is known as the internal control system in its application should take fairness and compliance as well as considering the size, complexity and nature of the tasks and functions of the Government Agencies. Internal control in government is considered very necessary to avoid actions that might be cheating or have been made by the various parties engaged in the world of government. In implementing these internal control, related parties refers to government regulation No. 60 of 2008. However, in reality this control is not maximized applied in government activities. Results of research conducted through the collection of data obtained through observation, documents and interviews. The results showed that the financial management process almost goes well, because there are things that may impede the process of managing their own will. But thanks to a sense of teamwork that is high on every employees in service income of the financial and property management areas in Tomohon, can make the work good. Runway and references used in the process of financial management in the life of the Financial Management and Revenue office property in the area Tomohon Pemendagri No. 13 of 2006. Keywords: Fiscal Management